Sexual revolutions in Cuba : passion, politics, and memory - Hamilton, Carrie, 1966- (Envisioning Cuba., 2012)
"In Sexual Revolutions in Cuba Carrie Hamilton delves into the relationship between passion and politics in revolutionary Cuba to present a comprehensive history of sexuality on the island from the triumph of the Revolution in 1959 into the twenty-first century. Drawing on an unused body of oral history interviews as well as press accounts, literary works, and other published sources, Hamilton pushes beyond official government rhetoric and explores how the wider changes initiated by the Revolution have affected the sexual lives of Cuban citizens. She foregrounds the memories and emotions of ordinary Cubans and compares these experiences with changing policies and wider social, political, and economic developments to reveal the complex dynamic between sexual desire and repression in revolutionary Cuba. Showing how revolutionary and prerevolutionary values coexist in a potent and sometimes contradictory mix, Hamilton addresses changing patterns in heterosexual relations, competing views of masculinity and femininity, same-sex relationships and homophobia, AIDS, sexual violence, interracial relationships, and sexual tourism. Hamilton's examination of sexual experiences across generations and social groups demonstrates that sexual politics have been integral to the construction of a new revolutionary Cuban society."--Book details